2016
DOI: 10.18235/0000493
|View full text |Cite
|
Sign up to set email alerts
|

Incumbent Advantage, Voter Information and Vote Buying

Abstract: work is licensed under a Creative Commons IGO 3.0 Attribution-NonCommercial-NoDerivatives (CC-IGO BY-NC-ND 3.0 IGO) license (http://creativecommons.org/ licenses/by-nc-nd/3.0/igo/legalcode) and may be reproduced with attribution to the IDB and for any noncommercial purpose, as provided below. No derivative work is allowed.Any dispute related to the use of the works of the IDB that cannot be settled amicably shall be submitted to arbitration pursuant to the UNCITRAL rules. The use of the IDB's name for any purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 23 publications
0
37
0
Order By: Relevance
“…The politicians themselves might also respond in ways that can dampen the effects of negative coverage. For instance, Cruz et al (2015) find evidence that politicians respond to information disclosure by engaging in more vote-buying. They implemented a field experiment in which they provided information to voters in the Philippines about the existence and importance of a large infrastructure public spending programme one week before a municipal election.…”
Section: Information About the Actions And/or Performance Of Politiciansmentioning
confidence: 99%
“…The politicians themselves might also respond in ways that can dampen the effects of negative coverage. For instance, Cruz et al (2015) find evidence that politicians respond to information disclosure by engaging in more vote-buying. They implemented a field experiment in which they provided information to voters in the Philippines about the existence and importance of a large infrastructure public spending programme one week before a municipal election.…”
Section: Information About the Actions And/or Performance Of Politiciansmentioning
confidence: 99%
“…Larreguy et al (2017), for example, showed that an anti-vote-buying campaign in Uganda increased vote buying by opposition candidates, which may explain why treatment reduced support for the incumbent. Cruz, Keefer, and Labonne (2016) showed that Filipino voters given congenial information about challengers' policy priorities still voted for the incumbent because the incumbent targeted them with increased handouts.…”
Section: Existing Studiesmentioning
confidence: 99%
“…A second generation of studies have adopted both experimental and 'ancillary' approaches to examine the electoral impacts of CCTs. 8 Notable examples are the field experiments by Galiani et al (2017) and Cruz et al (2016) conducted in Honduras and the Philippines, respectively. These studies highlight the role of information asymmetries between incumbents and voters in generating an electoral advantage to the incumbent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature has also covered questions related to individual voters' income (often referred to as 'pocketbook voting' (Grafstein, 2009;Kramer, 1983); the effects of economic conditions in general, as opposed to partisanship, ideology, or social status (Lewis-Beck and Stegmaier, 2000), and within that strand, studies that examine whether voting is retrospective or prospective (Fiorina, 1978;Fair, 1996;Healy and Malhotra, 2013;Lockerbie, 1991). Other relevant studies focus on quid pro quo arrangements, including clientelism (Wantchekon, 2003;Stokes, 2005) and the 'incumbency advantage' (Cruz et al , 2016;Mayhew, 2008). 24 The 'paradox of voting' reflects the insight that in large electorates the probability that a single vote is decisive is vanishingly small, and that hence, in the presence of even tiny voting costs, no one should vote (Feddersen, 2004) etc.…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation